2012
DOI: 10.1371/journal.pone.0037766
|View full text |Cite
|
Sign up to set email alerts
|

Disability, Home Physical Environment and Non-Fatal Injuries among Young Children in China

Abstract: ObjectivesWe compared the patterns of medically attended injuries between children with and without disabilities and explored the residential environment risks in five counties of Hubei Province in the People's Republic of China by a 1∶1 matched case-control study based on the biopsychosocial model of the International Classification of Functioning, Disability and Health – ICF.Methods1201 children aged 1–14 with disabilities and 1201 their healthy counterparts matched as having the same gender, same age, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
1
18
0
1
Order By: Relevance
“…Data about injury risk in individuals with disability in China are very limited [23]. Results reported here demonstrated a clear association between disability status (type and severity) and injury risk in this sample of Chinese pediatric population.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Data about injury risk in individuals with disability in China are very limited [23]. Results reported here demonstrated a clear association between disability status (type and severity) and injury risk in this sample of Chinese pediatric population.…”
Section: Discussionmentioning
confidence: 58%
“…Previous publications that reported an increased risk of injury in children with disability came from high income countries [15,1722]. In our recent publication about medically attended injuries among Chinese children with disability, we found that injury risk in children with disability is significantly higher than in children without disability [23]. We compared the patterns of injuries between children with and without disability and investigated the association between home environmental hazards and risk of nonfatal injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Geographically, the WHO region of the Americas was heavily represented, with ten studies in USA and one in Canada (Raman et al 2009), and the remaining four studies were from the WHO Asia and Western Pacific region (China, Hong Kong, Iraq, and Australia) (Othman and Kendrick 2013; Sherrard et al 2002; Tsang et al 2012; Zhu et al 2012). No eligible studies were found in the WHO Europe and Africa regions.…”
Section: Resultsmentioning
confidence: 99%
“…Injuries were defined if it met one of the following criteria: (1) Required medical attention or (2) Activities were restricted and rest was required for at least half a day because of sports injuries during the 12 months before the interview [5,6]. Using multistage cluster sampling, children age 8 to 15-years-old from 11 schools in Zunyi were recruited from June 2014 to July 2015.…”
Section: Methods and Resultsmentioning
confidence: 99%